Alarming Heat Wave-2024: The summer season in Pakistan - ahmed sheikh, khalil; Karim, Imran; ali shah, Syed Zulfiqar; Fatima, Muqadas; Ali, Mushahid; Faiza; Khushboo (Pakistan Journal of Medical & Health Sciences, 2024)
Heat waves are probably the most fatal kind of extreme weather event. The number of deaths is likely underreported, but hundreds of deaths have already been reported in most of the countries affected, such as Palestine, India, Pakistan, Bangladesh, Thailand, Myanmar, Cambodia, and the Philippines. It was also very hot, which hurt crops and decreased returns. It was also very hot, which meant that holidays had to be extended and institutions had to be closed in many countries, which affected millions of students. As far as extreme weather goes, a heat wave is the most dangerous type of weather incident. It is marked by a long time of very hot weather; regardless of high humidity.Some people use different words to describe the same "heat wave," because it depends on the normal weather in the area and the average temperature for the season. "Heatstroke" is described as a body temperature above 41°C, loss of sweating, and changes in mental status. It is linked to a lot of illness and death, especially if care is put off. Health officials say that nearly 700 people died in June during a terrible heat wave in Pakistan’s Sindh province. Most of the deaths that were reported happened in Karachi, mostly from heatstroke and being severely dehydrated. These deaths happened over three days. The city’s temperatures rose above 40°C, and on June 22, they hit 45°C, just below the city’s all-time high of 48 degrees Celsius that occurred on May 9, 19385